AUDIENCE MANAGEMENT AND MOTIVATION: RESEARCH ON HOW TO ENGAGE STUDENTS IN ENGLISH LANGUAGE CLASSES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This paper explores the strategies and theories related to audience management and motivation in English language classrooms. Emphasis is placed on effective engagement techniques that encourage active participation and long-term interest in learning English. Various motivational theories are discussed, and practical methods for enhancing student engagement are highlighted, supported by recent research findings.